1995
DOI: 10.1007/bf02381914
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and adrenocortical responses of male cynomolgus and lion-tailed macaques to social stimulation and group formation

Abstract: ABSTRACT. Several recent studies indicate that primate species may differ in behavioral, and in some instances physiological, responses to social manipulations. These differences in response dispositions have been interpreted as being based on temperamental differences among species. This report extends previous comparative studies of macaques by describing behavioral contrasts observed between males of two macaque species, lion-tailed and cynomolgus macaques, in response to social manipulations. Males were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 38 publications
1
22
0
2
Order By: Relevance
“…Another study has shown that Bornean orangutans (Pongo pygmaeus) at Chester Zoo, England, were disrupted by groups of visitors (Birke 2002). In addition, other factors have been reported to affect fecal glucocorticoid metabolite (fGCM) concentrations in primates such as sex (Honess and Marin 2006), age (Seraphin et al 2008;Van Cauter et al 1996), and changes in group composition (Clarke et al 1995;Heistermann et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study has shown that Bornean orangutans (Pongo pygmaeus) at Chester Zoo, England, were disrupted by groups of visitors (Birke 2002). In addition, other factors have been reported to affect fecal glucocorticoid metabolite (fGCM) concentrations in primates such as sex (Honess and Marin 2006), age (Seraphin et al 2008;Van Cauter et al 1996), and changes in group composition (Clarke et al 1995;Heistermann et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For example, group size and group composition resembling the natural social condition of a species can have positive effects on stress hormone levels (Clarke et al 1995;Reimers et al 2007). In this respect, improvements are especially needed in the housing systems of orangutans.…”
Section: Introductionmentioning
confidence: 99%
“…Pigtailed macaques are more prone to diarrhea than longtailed macaques, possibly reflecting greater stress levels in captivity [Hird et al, 1984]. Male longtailed macaques showed lower cortisol responses to group formation than did male lion-tailed macaques (M. silenus), although the latter were bolder [Clarke & Lindburg, 1993;Clarke et al, 1995]. Lion-tailed macaques are phylogenetically closely related to pigtailed macaques, whereas longtailed and rhesus macaques are in a separate species group, and bonnet macaques are in yet another group [Hoelzer & Melnick, 1996].…”
Section: Introductionmentioning
confidence: 99%
“…However, responses differed by species. The longtailed macaques showed more submissive behavior whereas lion-tailed macaques showed more aggressive behavior in response to the mirror (Clarke et al 1995).…”
Section: Normalized Repertoirementioning
confidence: 96%
“…When a mirror was attached to the cages of individually housed longtailed and lion-tailed macaques, response levels to the mirror were highest on day 1 of a 2-wk exposure period (Clarke et al 1995). However, it has been reported that interest can be restored simply by moving the mirror to a new location (Suarez and Gallup 1986) or by removing it for a period of time and then reinstating it (Gallup and Suarez 1991).…”
Section: Usagementioning
confidence: 98%